Reduced functional capacity is associated with the proportion of impaired myocardial deformation assessed in heart failure patients by CMR - Hashemi, Djawid; Doeblin, Patrick; Blum, Moritz; Weiss, Karl Jakob; Schneider, Matthias; Beyer, Rebecca; Pieske, Burkert; Duengen, Hans-Dirk; Edelmann, Frank; Kelle, Sebastian (Frontiers in Cardiovascular Medicine, 2023)
Aims: Heart failure (HF) does not only reduce the life expectancy in patients, but their life is also often limited by HF symptoms leading to a reduced quality of life (QoL) and a diminished exercise capacity. While the prognostic value of findings in cardiac imaging have been explored, the association of findings in routine parameters with symptoms and the wellbeing of patients is poorly studied. An imaging parameter indicating with power the clinical presentation of the patients would add to the descriptive value and make cardiac imaging more robust towards incomplete information. Methods and results: This prospective study conducted at two centres in Germany between 2017 and 2018 enrolled stable outpatient subjects with HF [n = 56, including HF with reduced ejection fraction (HFrEF), HF with mid-range ejection fraction (HFmrEF), and HF with preserved ejection fraction (HFpEF)] and a control cohort (n = 12). Parameters assessed included measures for external myocardial function, for example, cardiac index and myocardial deformation measurements by cardiovascular magnetic resonance imaging, left ventricular global longitudinal strain (GLS), the global circumferential strain (GCS) and the regional distribution of segment deformation within the LV myocardium, as well as basic phenotypical characteristics including the Minnesota Living with Heart Failure Questionnaire (MLHFQ) and the 6 minute walking test (6MWT). If less than 80% of the LV segments are preserved in their deformation capacity the QoL by MLHFQ, the subjective symptom burden (NYHA functional class), the shortness of breath during the 6MWT as well as the walking distance during the 6MWT are affected. Conclusion: The share of LV segments with preserved myocardial contraction allows to discriminate between symptomatic and asymptomatic subjects based on the imaging findings, even when the LV ejection fraction is preserved. This finding is promising to make imaging studies more robust towards incomplete clinical information.